If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X(6-X)=5.29
We move all terms to the left:
X(6-X)-(5.29)=0
We add all the numbers together, and all the variables
X(-1X+6)-(5.29)=0
We add all the numbers together, and all the variables
X(-1X+6)-5.29=0
We multiply parentheses
-1X^2+6X-5.29=0
a = -1; b = 6; c = -5.29;
Δ = b2-4ac
Δ = 62-4·(-1)·(-5.29)
Δ = 14.84
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-\sqrt{14.84}}{2*-1}=\frac{-6-\sqrt{14.84}}{-2} $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+\sqrt{14.84}}{2*-1}=\frac{-6+\sqrt{14.84}}{-2} $
| 3n2+11n-5000=0 | | X((6-x)=5.29 | | 5(3x+2=18 | | -4^x+1=3x-4 | | z*6=36 | | -4/5=32/x | | c-2c=0 | | 5(3x+2)=-4(2x-8)+1 | | x^2+12x-49=0 | | 3(a-4)=-18 | | 4a+7-2a-9=12 | | 2x+30)=(3x+5 | | (D^2+2D^2-15D)y=0 | | ((D^2+2D^2-15D)y=0 | | 3-(x+1/x+2)=(11x-2/x+2) | | 3(30a-7)-18=21 | | (x/x-3)=(3/x-3)+9 | | 2x-4(x-3)=3x-6-7x | | 5x+3+2x=6(x-1)+9 | | -4/5=x-1/2 | | 2x+5=x-16 | | x-12/3=14 | | 9x-43=x+37 | | 4a-11=9a+9 | | 3a-9=a+7 | | 12+3x=5x-10 | | 3y+6=6y-15 | | 12n-18=42 | | 8a+18=4a+2 | | 34=5n+9 | | 6x+15=4x+23 | | 3m-9=5m+9 |